1990
DOI: 10.1161/01.hyp.15.6.675
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic differences between black patients and white patients with essential hypertension. State of the art lecture.

Abstract: Physiological studies reported from our laboratory over the past several years have been reviewed and support epidemiological reports indicating that hypertensive cardiac and vascular disease runs a more severe course in the black patient Although comparison of systemic hemodynamics failed to demonstrate that, for any level of arterial pressure, the magnitude of total peripheral resistance (which is the hemodynamic hallmark of hypertensive disease) differed between black patients and white patients, there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…For example, chronically elevated vascular resistance has been implicated as one marker of heightened sympathetic activity in AAs. Several studies have reported exaggerated vasoconstriction and attenuated vasodilation in response to pharmacologic challenge (71-73) as well as associations of elevated vascular resistance with increased cardiac mass and left ventricle thickness in AAs (71). These and other findings have been recently summarized by Tehzarhada and colleagues (74), in which they note that differences in vascular activity exist between AAs and EAs and that these differences may contribute to the greater cardiovascular disease prevalence in AAs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, chronically elevated vascular resistance has been implicated as one marker of heightened sympathetic activity in AAs. Several studies have reported exaggerated vasoconstriction and attenuated vasodilation in response to pharmacologic challenge (71-73) as well as associations of elevated vascular resistance with increased cardiac mass and left ventricle thickness in AAs (71). These and other findings have been recently summarized by Tehzarhada and colleagues (74), in which they note that differences in vascular activity exist between AAs and EAs and that these differences may contribute to the greater cardiovascular disease prevalence in AAs.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Renal kallikrein could also be important as it generates the potent vasodilator and natriuretic peptide bradykinin which may in turn influence renin release indirectly through its effect on renal haemodynamics. In fact, in a comparative study 59 of blacks and whites matched for mean arterial pressure, at any level of blood pressure, renal vascular resistance was higher in the blacks and this was also associated with a significant reduction in renal blood flow. In turn this could account for the lower PRA in the blacks in view of the inverse relationship between renal vascular resistance and renin release.…”
Section: Hormones and Pra In Whites And Blacksmentioning
confidence: 95%
“…Left ventricular geometry in the non-dippers also showed increased concentric remodeling, concentric and eccentric hypertrophy. 27,28 and the pathogenicity of a non-dipping blood pressure profile in the Black population could play a key role in this. [15][16][17] However, data on cardiovascular target organ effects of NDP in the Black population are sparse.…”
Section: Resultsmentioning
confidence: 99%